2015
DOI: 10.1177/1359105315573438
|View full text |Cite
|
Sign up to set email alerts
|

Body image and college women’s quality of life: The importance of being self-compassionate

Abstract: Abstract:This study explores self-compassion as a mediator between body dissatisfaction, perceptions of inferiority based on body image, and quality of life, in 662 female college students. Quality of life was negatively correlated with body dissatisfaction and positively correlated with favourable social comparisons and selfcompassion. A path analysis revealed that, while controlling for BMI, selfcompassion mediated the impact of body dissatisfaction and perceptions of inferiority on psychological quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 47 publications
4
33
0
1
Order By: Relevance
“…Selfreassurance is more narrowly defined as the ability to be kind, caring and supportive when things go wrong (Gilbert, 2005(Gilbert, , 2009(Gilbert, , 2010. Selfcompassion seems to be positively linked to women's quality of life (Duarte et al, 2015a;Marta-Simões et al, 2016) and health-promoting behaviours (Dunne et al, 2016). Self-compassion also seems to be useful for BED treatment (Kelly and Carter, 2015;Kelly et al, 2014) and for dealing with body dissatisfaction in woman (Albertson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Selfreassurance is more narrowly defined as the ability to be kind, caring and supportive when things go wrong (Gilbert, 2005(Gilbert, , 2009(Gilbert, , 2010. Selfcompassion seems to be positively linked to women's quality of life (Duarte et al, 2015a;Marta-Simões et al, 2016) and health-promoting behaviours (Dunne et al, 2016). Self-compassion also seems to be useful for BED treatment (Kelly and Carter, 2015;Kelly et al, 2014) and for dealing with body dissatisfaction in woman (Albertson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Por sua vez, tanto os insatisfeitos pelo excesso quanto os insatisfeitos pela magreza apresentaram pior qualidade de vida nos domínios físico, psicológico e social, comparados aos satisfeitos. Embora tenham sido encontrados poucos estudos que investigaram as relações entre imagem corporal e qualidade de vida, as evidências disponíveis indicam fortemente que a insatisfação com a imagem corporal está associada negativamente à qualidade de vida em diferentes populações, bem como o contrário também é verdadeiro [22][23][24][25] . Tais resultados evidenciam a insatisfação com a imagem corporal como um problema de saúde pública atual, pois enfatizam que além do seu papel em outros desfechos "mais prejudiciais", frequentemente apontados pela literatura (tais como baixa autoestima, sintomas depressivos e de transtornos alimentares), conforme já alertaram Mond et al 23 , a mesma pode influenciar a qualidade de vida (que, por sua vez, engloba todos os desfechos citados).…”
Section: Discussionunclassified
“…Also, research has shown that self-compassion can buffer people against the impact of distressing and challenging situ-ations (Brion, Leary, & Drabkin, 2014;Leary, Tate, Adams, Batts, & Hancock, 2007). Namely, and in what concerns body image, a recent study showed that, for normal-weight college students, the harmful effect of negative experiences related to the body on QoL may be mitigated by the ability to be self-compassionate (Duarte et al, 2015). In contrast, recent studies have shown that body image dissatisfaction may become problematic when it becomes linked to maladaptive emotion regulation strategies (Pinto-Gouveia et al, 2014).…”
mentioning
confidence: 99%
“…Also, results from different studies emphasized the relationship between body dissatisfaction and quality of life (QoL) and well-being impairment, showing that higher body dissatisfaction E-mail: ines.almeidatrindade@gmail.com was associated with decreased levels on all domains of QoL, especially psychosocial functioning (Duarte, Ferreira, Trindade, & Pinto-Gouveia, 2015;Mond et al, 2013). In addition, the 2 C. Ferreira et al degree of mental health impairment has been shown to be proportional to the degree of body dissatisfaction (Mond et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation